Bacterial diversity in the honey sac during bee foraging on winter-flowering flora and dominant Bacillus subtilis inhibits Hafnia alvei - Wang, Miao; Zhao, Wenzheng; Zhou, Danyin; Huang, Jian (Frontiers in Insect Science, 2025)
BackgroundThe bacterial diversity of two bee species in the process of honey collection during the flowering season of three different floral sources in the winter was studied. The common bacterium in all samples was Bacillus subtilis.MethodsIn the present study, we collected nectar, honey sacs, and fresh honey during the winter flowering season of Agastache rugosa, Prunus cerasoides, and Brassica rapa. The pure culture method was used to count and analyze the number of bacteria, they were identified using 16S rRNA sequencing, similarities were compared in NCBI, and the common dominant bacterial species B. subtilis in all samples using phylogenetic analysis and intersection analysis were determined to conduct further bacteriostatic experiments.ResultsThe results showed that the most abundant quantity of bacteria could be found in the honey sacs, compared to in nectar or fresh honey. At the same time, the highest abundance of bacteria could be found in the honey sacs of A. cerana when collected on Brassica rapa, while the highest abundance of bacteria could be found in the honey sacs of A. mellifera when collected on Prunus cerasoides and Agastache rugosa. A total of 33 bacterial species were isolated, with variations in their distribution across different sample types and sources. The inhibitory effect of 10-1-10-5 on Hafnia alvei by B. subtilis was very significant.ConclusionsB. subtilis was identified in all sample sources, indicating the potential importance of B. subtilis as a probiotic in the bee gut for honey production, and B. subtilis could promote the disease resistance and health of honeybees in winter.